A Latex Bead-Based Flow Cytometric Immunoassay Capable of Simultaneous Typing of Multiple Pneumococcal Serotypes (Multibead Assay) - Park, M. K. (American Society for Microbiology, 2000)
A simple and rapid method of simultaneously determining 15 Streptococcus pneumoniae serotypes was developed. Fifteen latex beads of different sizes and different red fluorescence levels were coated with 1 of 15 serotypes (1, 3, 4, 5, 6A, 6B, 7F, 9N, 9V, 14, 18C, 19A, 19F, 22F, and 23F) of pneumococcal capsular polysaccharide (PS). The bead mixture was incubated with individual pneumococcal lysate, a pool of rabbit antisera capable of binding the 15 serotypes, and fluorescein (green fluorescence)-conjugated anti-rabbit antibody. Bead size, red fluorescence, and green fluorescence were measured in a single flow cytometer run. The green fluorescence of the beads was inhibited only when there was a serotypic match between PS on the bead and PS in the pneumococcal lysate. This method distinguished cross-reactive serotypes and correctly identified the serotypes in 100% of 86 pneumococcal isolates tested.